The Impact Of Financial Literacy, Financial Attitudes And Financial Behaviour On MSMEs Growth - Fitriyah; Hermawan, Agus; Sudarsono, Naswan (Publisher Cv. Inara, 2023)
This study is aimed at investigating the effect of financial literacy, financial attitudes and financial behaviour on the growth of micro- and small-sector enterprises (MSMEs) in Trenggalek Regency, Indonesia. Data was collected using a structured questionnaire and a Likert scale. The analysis technique used in this research is partial least squares analysis using structural equation models (SEM-PLS). The results showed that financial literacy and financial behaviour has an effect on the growing of MSMEs In Trenggalek Regency. MSME managers who have a high level of literacy will have knowledge, skills and beliefs that will influence their attitudes and behaviour in making financial decisions. Financial attitudes have no effect on MSME growth. Although MSME owners have positive attitudes towards finance, they may be unable or unwilling to take financial steps that support the growth of their business